Microbiota intestinal y su relación con el cáncer colorrectal: Revisión sistemática - Troya Abad, Mireya Marixa (2024)
The intestinal microbiota performs essential functions for the proper functioning of the body. However, a state of dysbiosis can contribute to the development of colorectal cancer. This study aims to describe the composition of the intestinal microbiota in patients with colorectal cancer and to list the protective and risk factors associated with the development of this disease. An exhaustive search was conducted using combinations of MeSH terms and the boolean operator "and" in electronic databases: Scielo and Pubmed. The PRISMA method was applied for screening, selecting publications from the year 2013 onwards, excluding grey literature. Twenty-six studies were included in this systematic review, evaluated using the JBI tool, demonstrating a low risk of bias. It was identified that the intestinal microbiota in patients with colorectal cancer had a predominance of pathogenic bacteria suchas Fusobacterium nucleatum, Bacteroides fragilis, Escherichia, Shigella and a lower amount of Peptostreptococcus, Streptococcus salivarius, Streptococcus anginosus, Prevotella intermedia, Ascomycota, and Basidiomycota. The identified protective factors included a healthy diet, exercise, and the consumption of probiotics and prebiotics. The evidenced risk factors are age, sex, genetics, obesity, overweight, tobacco consumption, alcohol, and the intake of red meat and ultra-processed foods